2000
DOI: 10.1046/j.1365-2958.2000.02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of SarH1, a new global regulator of virulence gene expression in Staphylococcus aureus

Abstract: The global regulators agr (accessory gene regulator) and sarA (staphylococcal accessory regulator) have been reported to be both activators and repressors of virulence gene expression in Staphylococcus aureus. How the effector of the agr system, RNAIII, interacts with target gene promoters is unknown. SarA, on the other hand, is a DNA‐binding protein, which binds to conserved DNA motifs immediately upstream of both positively and negatively regulated promoters. Here, we searched for additional regulators that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
233
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(269 citation statements)
references
References 47 publications
(67 reference statements)
35
233
0
Order By: Relevance
“…Regulation of the sarA family of genes is intertwined in nature (Manna & Cheung, 2006a, b). It should be stressed that sarS is transcribed in the early growth phase and tapers off in transcription at the postexponential and stationary phases of growth in RN6390 strain Tegmark et al, 2000). In the future, we will be analysing various sarA family mutant strains of S. aureus from different genetic backgrounds to determine if there is any variability of the data presented in this report.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Regulation of the sarA family of genes is intertwined in nature (Manna & Cheung, 2006a, b). It should be stressed that sarS is transcribed in the early growth phase and tapers off in transcription at the postexponential and stationary phases of growth in RN6390 strain Tegmark et al, 2000). In the future, we will be analysing various sarA family mutant strains of S. aureus from different genetic backgrounds to determine if there is any variability of the data presented in this report.…”
Section: Discussionmentioning
confidence: 96%
“…These results are consistent with our earlier finding that most of the SarA paralogues regulate each other. Furthermore, the SarA paralogues involved in virulence gene regulation are intertwined: for example, sarR represses SarA expression , sarA represses and rot activates sarS expression Said-Salim et al, 2003;Tegmark et al, 2000), sarA negatively regulates sarT and sarT activates sarS , both SarA and MgrA repress sarV (Manna et al, 2004), while MgrA activates sarX transcription (Manna & Cheung, 2006b). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within each winged helix motif is a helix-turn-helix motif (α3α4) and a β-hairpin turn wing (β2β3), both of which are putative DNA binding domains (Liu et al, 2006). SarS is a 250-residue DNA binding protein that activates protein A gene (spa) transcription (Table 1) (Tegmark et al, 2000;Cheung et al, 2004). Unlike the dimeric structures of SarA and SarR, SarS forms a monomeric structure with two homologous but non-identical halves (Fig.…”
Section: Structure Of the Sara Protein Familymentioning
confidence: 99%
“…SarS is a 250-residue two-domain SarA homolog that activates spa and represses hla transcription (Tegmark et al, 2000;Cheung et al, 2004)}. Transcriptional analysis indicated that sarS is repressed by agr and mgrA and activated by ClpXP protease (Frees et al, 2005).…”
Section: C Other Sara Homologsmentioning
confidence: 99%